Administrative Archives from the City of Assur in the Middle Assyrian Period - Postgate, John Nicholas
36*-40* auch arabisch u.d.T. si?ill?t al-ma?f???t min mad?nat ’?šš?r min al-’ahd al-’?šš?r? al-was??.